RESPON PENYEBERANG JALAN TERHADAP FASILITAS JEMBATAN PENYEBERANGAN ORANG(JPO) DI KOTA PEKANBARU - Silvia, Novita; ", Yoserizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research entitled Community Response to Crossing People Bridge Facility (JPO) In Pekanbaru City. This study aims to determine the public response to the facility Crossing People (JPO) in Pekanbaru City. The way of sampling or respondents is done by incidental sampling technique, where the determination of respondents done by chance when viewed by people who happened to be found suitable as a source of data in the field as many as 100 people. The researcher took samples using Slovin formula as many as 50 people. The theory used in this research is the theory of behavior, response, and perception. The research method used is descriptive quantitative method.From the results of this study is that seen from the recapitulation agreed on the facility Crossing Bridge People (JPO) with an average value of 4.20 with the most influencing indicator is the Bridge Construction Crossing People (JPO) looks strong and the recapitulation agreed on the response of the pedestrian to the Bridge Crossing Facility (JPO) facility with an average of 4.02 with the most influencing indicator is the dubious People Crossing Bridge (JPO) construction. In the t test, thitung -0.989 more kecildari ttabel 2.011 with a significant level of 0.328 greater than 5%. Then Ho is rejected and Ha accepted, meaning that the variables of JPO facilities affect the community response. This determines that the Bridge Over Cross (JPO) facility affects the public response, on R-square (coefficient of determination) of 0.020. This means that the JPO facility contributes to the response of the community at 2.0%, while the rest (100% -2.0%) = 98% is influenced by other variables outside the variables in this study, the better the Bridge Crossing Facility JPO) the better crossers response. Keywords: Response, Crossing Bridge People